DETERMINANT MODEL OF COMPANY VALUE WITH PROFITABILITY AS A MEDIATION VARIABLE - Parlindungan Sipahutar, Roni; Firza Alpi, M.; Ammy, Baihaqi (CV. Radja Publika, 2021)
This study aims in general to produce a determinant model of firm value with profitability as a mediating variable. The population in this study were all general pharmaceutical sector companies listed on the Indonesia Stock Exchange in 2013-2018. Sampling in this study used a census technique, which was to place the entire population into an observation sample. The sampling method used is purposive sampling with a total sample of 6 Pharmaceutical Companies Listed on the Indonesia Stock Exchange and data from 2013 – 2018. Data collection is carried out on the Indonesia Stock Exchange (IDX) with the website www.idx.co. en. Data analysis techniques in this study are descriptive statistics, multiple regression analysis and path analysis to test the mediating variables. The results of the study show that liquidity has a negative and significant effect on firm value. Meanwhile, profitability has no significant effect on firm value. The liquidity has a positive and significant effect on firm value with profitability as an intervention variable.